2017
DOI: 10.1080/17533015.2017.1334002
|View full text |Cite
|
Sign up to set email alerts
|

Non-clinical community interventions: a systematised review of social prescribing schemes

Abstract: Background: This review focused on evaluation of United Kingdom social prescribing schemes published in peer-reviewed journals and reports. Schemes, including arts, books, education and exercise "on prescription" refer patients to community sources of non-clinical intervention. Method: A systematised review protocol appraised primary research material evaluating social prescribing schemes published 2000-2015. Searches were performed in electronic databases using keywords, and articles were screened for evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
256
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(285 citation statements)
references
References 59 publications
4
256
0
2
Order By: Relevance
“…1,2,3 Nevertheless, it is important to improve understanding of the mechanisms by which art-making may improve health and wellbeing in order to both build supporting explanatory models and to improve the efficacy of public health interventions. The current paper focuses on art-making as a personal resource in everyday life and its associations with psychological indices of wellbeing (both 'in the moment' and longer term), in order to explore the psychological mechanisms by which art-making promotes wellbeing in this context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3 Nevertheless, it is important to improve understanding of the mechanisms by which art-making may improve health and wellbeing in order to both build supporting explanatory models and to improve the efficacy of public health interventions. The current paper focuses on art-making as a personal resource in everyday life and its associations with psychological indices of wellbeing (both 'in the moment' and longer term), in order to explore the psychological mechanisms by which art-making promotes wellbeing in this context.…”
Section: Introductionmentioning
confidence: 99%
“…6,3 Further benefits of art-making include increased positive affect, self-esteem, and improved social skills and working memory. 1,6,7,8,9 Various models have been proposed to explain why and how participatory arts may improve wellbeing. 10 For example, early models to explain the effects of expressive writing on wellbeing proposed that art enables catharsis, whereby disclosing once inhibited affective content reduces stress and improves immune system functioning.…”
Section: Introductionmentioning
confidence: 99%
“…A review of social prescribing found that schemes demonstrated variable sustainability, and only 40% had been evaluated using a plethora of assessment types, two-thirds of which employed qualitative methods and a one third used quantitative methods. 1 The review found that the most effective referral route involved a local link-worker or navigator placed in a primary care or third sector organisation, able to keep abreast of non-clinical community interventions and make appropriate referrals. 1 Public Health england (PHe) stated that 'communities, both place-based and where people share a common identity or affinity, have a vital contribution to make in health and wellbeing' and that the 'assets within communities, such as the skills and knowledge, social networks and community organisations, are building blocks for good health' (p. 5).…”
mentioning
confidence: 99%
“…1 The review found that the most effective referral route involved a local link-worker or navigator placed in a primary care or third sector organisation, able to keep abreast of non-clinical community interventions and make appropriate referrals. 1 Public Health england (PHe) stated that 'communities, both place-based and where people share a common identity or affinity, have a vital contribution to make in health and wellbeing' and that the 'assets within communities, such as the skills and knowledge, social networks and community organisations, are building blocks for good health' (p. 5). 2 Social prescribing aligns with local and national agendas to improve health and wellbeing and reduce health inequalities because it is 'patient-centred; not just what the NHS can do; it is a conduit for involving patients in their community and opening the channels between service sectors' (p. 4).…”
mentioning
confidence: 99%
“…Recent reviews of social prescribing evaluations and research indicate multiple benefits reported by participants and referrers directly engaged in social prescribing, including: increases in self-esteem and confidence; improvements in psychological or mental wellbeing; reduction in anxiety and depression; improvements in physical health and lifestyle; reduction in GP visits and referrals; reduction in social isolation and loneliness; learning and acquisition of new skills (see Chatterjee et al 2017). Arts on Prescription, one of the earliest models of social prescribing, was established in the mid-1990s and was developed as a practice involving creative art workshops to support patients with anxiety and other mental health challenges [See Box 1].…”
Section: How Can People Benefit From Social Prescribing?mentioning
confidence: 99%